TEORI DAN PRAKTIK PENENTUAN AHLI WARIS ASHOBAH DALAM KONSEP SYAJAROTUL MIRATS - Raja Ritonga (Nizham Jurnal Studi Keislaman, 2022)
In Islamic inheritance, the process of determining the heirs is carried out before the distribution of inheritance. The categories of heirs are grouped based on their status and kinship to the heirs. Ashobah is a group of heirs who are understood as recipients of the remaining assets. However, the ashobah heirs do not always receive the rest of the property, but the ashobah group can also not get an inheritance at all. This study aims to describe the theory and practice of determining Ashli ​​heir ashobah based on the concept of syajarotul mirats. This study uses a qualitative method with the type of library research. All the data collected were analyzed descriptively. The results of the study explain that the heirs of ashobah in getting an inheritance are between three possibilities. First, ashobah gets all the inheritance. Second, ashobah get the rest of the inheritance after the ashabul furudh group. Third, ashobah does not inherit at all. Furthermore, there is only one heir who becomes ashobah and there cannot be two ashobah. In the concept of syajarotul mirats, all types of ashobah are judged based on jihhah, qorobah and quwwatul qorobah on the bunuwah, ubuwah, ukhuwah and 'umumah lines.